Performance and Emission Analysis of Common Rail Diesel Engine with Microalgae Biodiesel - Yenda Srinivasa Rao; Tsegaye Getachew Alenka (Journal of Engineering)
Modern common rail diesel engines are normally optimized with commercial diesel. As a result, the engine control unit’s calibration is established to achieve the best compromise between performances and exhaust pollutants. Biodiesel has a faster combustion rate and higher combustion chamber temperature than commercial diesel, which necessitates the injection of higher fuel volumes to compensate for the lower calorific value of biodiesel compared to regular diesel. This study showed that by adjusting the mapping of the engine control unit according to the fuel utilised, it is possible to improve the emissions and performance of a common rail diesel engine running on pure Botryococcus braunii algae oil biodiesel or a blend of biodiesel and commercial diesel.